Adaptable and Reprogrammable Surfaces. Issue 40 (15th August 2019) - Goldmann, Anja S.; Boase, Nathan R. B.; Michalek, Lukas; Blinco, James P.; Welle, Alexander; Barner‐Kowollik, Christopher
Abstract: Establishing control over chemical reactions on interfaces is a key challenge in contemporary surface and materials science, in particular when introducing well‐defined functionalities in a reversible fashion. Reprogrammable, adaptable and functional interfaces require sophisticated chemistries to precisely equip them with specific functionalities having tailored properties. In the last decade, reversible chemistries—both covalent and noncovalent—have paved the way to precision functionalize 2 or 3D structures that provide both spatial and temporal control. A critical literature assessment reveals that methodologies for writing and erasing substrates exist, yet are still far from reaching their full potential. It is thus critical to assess the current status and to identify avenues to overcome the existing limitations. Herein, the current state‐of‐the‐art in the field of reversible chemistry on surfaces is surveyed, while concomitantly identifying the challenges—not only synthetic but also in current surface characterization methods. The potential within reversible chemistry on surfaces to function as true writeable memories devices is identified, and the latest developments in readout technologies are discussed. Finally, we explore how spatial and temporal control over reversible, light‐induced chemistries has the potential to drive the future of functional interface design, especially when combined with powerful laser lithographic applications. Abstract : Spatial and temporal control over the physical and chemical properties of surfaces and interfaces is a key challenge in contemporary materials science. A critical survey of the state‐of‐the‐art is presented, identifying key challenges and future directions in existing synthetic and characterization methods.